The impact of climate change on the development of water resources - M.D. Teweldebrihan; M.O. Dinka (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: River basin ecology changes frequently when water resources are developed more. In order to meet human needs, the influence of climate change on river flow and hydrological structures should be understood. Population growth, corresponding economic expansion, and irrigation-related factors for food production all contribute to rising water demand. Consequently, the water availability becomes a scarce resource, when the water demand exceeds the supply. Hence, the understanding the interaction between water, ecosystem and society is a key factor in sustainable water resource development, management and utilization.METHODS: This study evaluates the effects of climate change on the water resource development of the Dhidhessa River Basin. The degree of hydrologic modification was estimated using the Indicator of Hydrologic modification programs. Based on the analysis, the study looked into how variations in rainfall and temperature might affect the river’s flow and Dhidhessa basin. Stakeholder analysis was used to identify seven types of stakeholders who expressed interest in the Dhidhessa sub basin.FINDING: The results indicate that the basin experienced a decrease in water level and river flow as a result of climate change. This drop-in water level and river flow can be attributed to the anticipated change in climate caused by variations in rainfall. The Dhidhessa River Basin, located near the Dembi gauge station, was particularly vulnerable to these changes in flow. Interestingly, the degree of flow alteration was found to be relatively low throughout most of the months. In terms of stakeholder distribution, municipal and community governments accounted for 17.3 percent and 25.4 percent, respectively. Additionally, organizations with investors, ministries, and certain government agencies represented 37.4 percent of the articles, while foreign actors and religious organizations accounted for 19.9 percent.CONCLUSION: The research findings indicate that the water balance in the Dhidhessa basin may be affected by climate change in the coming century. Thus, the variation in rainfall and temperature might affect the river flow. However, it is impossible to determine this change's direction definitively until the model results are assessed under various scenarios. Therefore, the virtual future of socio-hydrologic assessment and better integration of stakeholders is needed to understand the dynamics in the basin for sustainable water resource development and management.